2020
DOI: 10.3389/fmars.2020.567228
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification Mitigates the Negative Effects of Increased Sea Temperatures on the Biomineralization and Crystalline Ultrastructure of Mytilus

Abstract: Negative impacts of global climate change are predicted for a range of taxa. Projections predict marked increases in sea surface temperatures and ocean acidification (OA), arguably placing calcifying organisms at most risk. While detrimental impacts of environmental change on the growth and ultrastructure of bivalve mollusk shells have been shown, rapid and diel fluctuations in pH typical of coastal systems are often not considered. Mytilus edulis, an economically important marine calcifier vulnerable to clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The combined impacts of OA and OW have been addressed with contrasting responses, such that the effects of OA and OW are either exacerbated (e.g., Di Santo 2015;D'Amario et al, 2020;Zittier et al 2018;Rodolfo-Metalpa et al, 2011) or ameliorated (e.g., Kroeker et al 2014;Knights et al, 2020;García et al, 2015;Jiang et al, 2018) in the presence of the other stressor (). Meta-analyses have suggested that the combined impacts of OA and OW on species physiology are especially devastating for the larval stages of many species (Przeslawski et al, 2015;Kroeker et al, 2013), presenting a major bottleneck for population persistence under changing oceanic conditions (Przeslawski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The combined impacts of OA and OW have been addressed with contrasting responses, such that the effects of OA and OW are either exacerbated (e.g., Di Santo 2015;D'Amario et al, 2020;Zittier et al 2018;Rodolfo-Metalpa et al, 2011) or ameliorated (e.g., Kroeker et al 2014;Knights et al, 2020;García et al, 2015;Jiang et al, 2018) in the presence of the other stressor (). Meta-analyses have suggested that the combined impacts of OA and OW on species physiology are especially devastating for the larval stages of many species (Przeslawski et al, 2015;Kroeker et al, 2013), presenting a major bottleneck for population persistence under changing oceanic conditions (Przeslawski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another study with Mytilus, which used a similarly extreme upper CO2 level, found that the resultant acidification (or, as we prefer, reduced alkalinity) suggests a complex relationship between calcification and the various active components of climate change that might ease the negative effects of increased sea temperatures on biomineralisation in the mussel [37]. Even greater complexities become evident in organisms, like calcifying phytoplankton (coccolithophores), that bring photosynthesis into the mix of variables [38].…”
Section: Fitzer Et Al (2016)mentioning
confidence: 88%
“…Fitzer et al (2016) have demonstrated significant changes in the hydrated and dehydrated forms of amorphous calcium carbonate in the crystalline layers of mussel (Mytilus edulis) shells cultured under acidification conditions. However, there is evidence that, in Mytilus, acidification eases the negative effects of increased sea temperatures on biomineralization, suggesting a complex relationship between calcification and the various components of climate change (Knights et al, 2020). Adverse effects of present day ocean acidification are clearly seen to impact the viability of symbiotic algae of coral and giant clams, and in those cases, too, are interwoven with elevated temperatures and light levels in relatively shallow tropical waters.…”
Section: Fishing With Dolphinsmentioning
confidence: 99%